DESKRIPSI FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN ANAK DALAM MENGHADAPI MENARCHE DI SD NEGERI 1 KRETEK KECAMATAN PAGUYANGAN KABUPATEN BREBES TAHUN 2011 - Jayanti, Nur Fitri; Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
Menarche is discharge menstruasion blood that happened for the first time in normal woman, its started from 9-17 years old, it’s special characteristic of healty maturation woman and not pregnant. Menarche is influential about the charge of alferation mental’s child that accept is change if positive or want to receive and ready to face menarche, and change in negative direction or refuse and not ready to face menarche phsycology process. Child readiness to face menarche is influenced by some factors, such as: age, source information and child attitude. This research to have a purpose know ilustration of the factors that influnce child readiness to face menarche based on age, source information and chid attitude. Kind of research that used is descriptive, time approaching cross sectional, the sampel are 52 respondent, using univariat analysis. Result of research child readiness to face menarche based on age majority 13 children in 10 yaers old (27,08%) is not ready to face menarche, based on the source information there are 17 children (56,25%) is not ready to face menarche got information from their friend, while 38 children (79,17 %) have bad attitude about menarche. Most of children are not ready to face menarche caused less knowledge that received by the child about menarche and the earlier age when child face menarche. Should by school, family and Departement of Healty give knowledge about menarche earlier in order that they are ready to face menarche.Keywords : Readiness, Menarche